2004
DOI: 10.1200/jco.2004.08.116
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Escalated Doses of Weekly Intravenous Infusion of CCI-779, a Novel mTOR Inhibitor, in Patients With Cancer

Abstract: CCI-779 displayed no immunosuppressive effects with manageable and reversible adverse events at doses up to 220 mg/m(2), the highest dose tested. Based on our results, weekly doses of 25, 75, and 250 mg CCI-779 not based on classical definitions of maximum-tolerated dose are being tested in phase II trials in patients with breast and renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
288
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(304 citation statements)
references
References 29 publications
11
288
1
4
Order By: Relevance
“…In the second study, patients received temsirolimus weekly as a 30 minute infusion over a dose range of 7.5 to 220 mg/m 2 /week. 72 At 220 mg/m 2 /week, dose-limiting manic-depressive syndrome, stomatitis, and asthenia seen in two of nine patients limiting further dose escalation. The pharmacokinetic profile and the MTD of temsirolimus weekly intravenously in patients with recurrent malignant gliomas taking enzyme-inducing anti-epileptic drugs (EIAEDs) has also been evaluated.…”
Section: Temsirolimus (Cci-779)mentioning
confidence: 97%
“…In the second study, patients received temsirolimus weekly as a 30 minute infusion over a dose range of 7.5 to 220 mg/m 2 /week. 72 At 220 mg/m 2 /week, dose-limiting manic-depressive syndrome, stomatitis, and asthenia seen in two of nine patients limiting further dose escalation. The pharmacokinetic profile and the MTD of temsirolimus weekly intravenously in patients with recurrent malignant gliomas taking enzyme-inducing anti-epileptic drugs (EIAEDs) has also been evaluated.…”
Section: Temsirolimus (Cci-779)mentioning
confidence: 97%
“…A case report of a patient with mIAS for whom treatment included topical dexamethasone, intralesional injections of the corticosteroid triamcinolone, and magic mouthwash oral rinse demonstrated significant improvement in the signs and symptoms of mIAS lesions 47. However, the collective studies report an overall lack of effectiveness for managing mIAS with the prophylactic use of other oral rinses, such as antiseptic‐based 51 or sodium bicarbonate‐based mouthwashes 52.…”
Section: Preventing and Treating Mtor Inhibitor–associated Stomatitismentioning
confidence: 99%
“…[8][9][10] We have previously shown that rapamycin induces apoptosis in precursor B ALL lines in vitro and has in vivo activity in transgenic mice with pre-B leukemia/lymphoma. 11 Second generation MTIs, CCI-779 and RAD-001, are currently in phase 1 to phase 3 clinical trials in patients with various cancers, [12][13][14][15] but preclinical studies have not previously been performed in primary human ALL.…”
Section: Introductionmentioning
confidence: 99%